Pengaruh Kepuasan Kerja Terhadap Disiplin Kerja Karyawan Pada Resort Dangau Kota Singkawang - Sudarwin A (JURNAL MANAJEMEN MOTIVASI, 2014)
The purpose of this study was to determine the effect of job satisfaction on the work discipline Resort Dangau Singkawang. This deskritptif study used a sample of the population and the use of questionnaires as the principal means of collecting data. The population is all employees at the Resort loom Singkawang. The sample is taken using a sampling technique that is saturated sampling technique when all members of the population used as a sample. Analysis techniques used in this research is to use a simple linearregression. The results showed that job satisfaction have an influence on work discipline which the test results showed 23.504 F count> F table 4.034. And has a significance value of 0.000, which is smaller than 0.05. Simple Linear Regression equations showed the following results, y = 0.893 + 0.840 X. The regression coefficient (β) 0.893 explained that when employee satisfaction at Resort Dangau Singkawang amounted to 0 (zero), then the discipline of employees at Resort loom Singkawang by 0,893. If the jobsatisfaction of employees at the Resort loom Singkawang increased by one unit then the discipline of employees at the Resort loom Singkawang will increase by 0.840 units. Correlation and Determination of test results showed that the value of R = 0.562, while the value of the coefficient of determination (R2) obtained at 0.315. This means that 31.5% (1 x 0.315 x 100%) of employees at the Resort Dangau Singkawang can be explained by employee satisfaction at Resort loom Singkawang, while the remaining 68.5% (1 to 0.315 x 100 %) employees' discipline Resort loom Singkawang is influenced by other variables not examined in this study.